Natural History of Periodontal Disease: a systematic review (Research, Society and Development, 2020)
Introduction: periodontal diseases consist of pathologies of chronic course, with a multifactorial etiology, which can cause several harm to body health, as it is associated with other systemic diseases. Objective: to perform a literature review on the Natural History of Periodontal Disease. Materials and methods: the study is characterized by a systematic review of the literature, based on the theme of periodontal diseases. The Scielo database was adopted as a research source, and the publication interval of the articles was limited between 2015 and 2019. Results: 298 articles were found and, after applying the eligibility criteria, 12 articles were analyzed. From there, it was possible to determine the Natural History of Periodontal Disease, from the periods of pre-pathogenesis and pathogenesis, in addition to the conceptual map and analysis of the hypothetical causal model. Conclusion: it was possible to consider that periodontal diseases are mainly related to poor hygiene and lack of knowledge, in addition to multiple associated factors.